The impact of antihyperlipidemic drugs on the viral load of patients with chronic hepatitis C infection: a meta‐analysis. Issue 8 (18th June 2014) - Grammatikos, G.; Farnik, H.; Bon, D.; Böhlig, A.; Bader, T.; Berg, T.; Zeuzem, S.; Herrmann, E.
Summary Several studies investigating the role of statins and fibrates in chronic hepatitis C virus (HCV) infection offered so far conflicting evidence regarding the antiviral potency of these medications, whereas combination of these drugs with pegylated interferon and ribavirin improved in some trials therapeutic outcome. We conducted a literature search to identify trials that included monoinfected HCV patients, treated with statins or fibrates as monotherapy with the primary end point of our meta‐analysis being the quantitative change of HCV‐RNA induced by these medications. Logarithmic changes of the viral load (ΔlogVL) and confidence intervals (CIs) were calculated according to the DerSimonian‐Laird estimate. Statistical heterogeneity was assessed with the I² statistic. We identified eight observational studies that evaluated the potency of bezafibrate and different statins as monotherapy to induce a significant reduction of HCV‐RNA in HCV‐monoinfected patients (n = 281). Overall, a significant reduction of viral load with mean 0.19 [log10 IU/mL] (95%‐confidence interval, (CI) 0.11–0.28) could be observed when antihyperlipidemic medications were administered. Bezafibrate featured the highest antiviral efficacy (0.45 log10 reduction, 95%‐CI, 0.17–0.72) among all medications and fluvastatin (0.20 log10 reduction, 95%‐CI, 0.09–0.31) among all statins tested. Based on meta‐analysis, fibrates and statins induce a reduction of HCV viral load. We suggest that the addition of statins and fibrates to antiviral regimes, especially in HCV patients with concomitant dyslipidemia, could beside the established reduction of cardiovascular risk increase the potency of antiviral therapy.